Device for Cleaning Cotton from Small Pollution Experimental Test Results Analysis - Solijonovich, Jamolov Abdurakhmon (American Journal of Biodiversity, 2026)
In the theoretical study of the proposed cotton cleaning device, in order to increase the usefulness of the mesh surface, the mesh surface is made in an oval shape, and at the same time, the drum is placed obliquely to increase the total cleaning surface. The arrows placed in the drum are installed vertically, which makes it easier to pick the cotton inside the drum and increases the level of cleaning. It is desirable to increase the quality of cleaning cotton from impurities and its work efficiency by introducing a cotton cleaning device with an oval-shaped mesh surface to the cotton cleaning plant.